Causes of death among the Ceasars (27 BC-AD 476) - Francois P. Retief; Louise Cilliers (Acta Theologica)
The Roman Empire was ruled by 77 emperors between 27 BC and AD 476 (503 years); 18 (23,4%) of them held sway during the Early Empire (27 BC–AD 193, 220 years), and 59 (76,6%) during the Late Empire (193-476, 283 years). On the average emperors in the Early Empire ruled for a longer period (12,7 years as against 6,0 years), and died slightly later (53,4 years as against 46,0 years) than subsequent emperors. During the Early Empire 55,6% of the emperors died of natural causes or illness, as against 25,4% during the Late Empire. Of the second group more were murdered or executed (55,9% versus 33,3%) and more died on the battlefield (5 versus none). The incidence of suicide was slightly higher among the early emperors (11,1% as against 6,8%). Seven emperors abdicated before death brought an end to their rule — only 2 died of natural causes. 30 of the 33 murdered were killed by the sword or dagger (5 were beheaded), one was strangled, one was hanged and one was killed by stoning.